PENGARUH PERTUMBUHAN PENJUALAN DAN RETURN ON ASSET TERHADAP NILAI PERUSAHAAN (Studi Pada Perusahan Manufaktur Sub Sektor Makanan dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2020) - Raden Wulan Saparinda; Aep Muhammad Jaelani (JURNAL AKUNTANSI DAN SISTEM INFORMASI, 2022)
Abstract: The purpose of this study was to determine the effect of sales growth and Return On Assets (ROA) on the study firm value of food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The research method used was descriptive analysis technique and verification. The population in this study is the food and beverage sub-sector listed on the Indonesia Stock Exchange for the 2016-2020 period. With a population of 32 companies, the number of samples is 12 companies. The analytical tool used in this study is multiple linear regression analysis, coefficient of determination analysis and hypothesis testing, in this study using a partial t test with the help of the Eviews 10 program. The results of this study indicate that sales growth has no significant effect on firm value. Meanwhile, return on assets has a significant and positive relationship to firm value.